Memahami Bid‘ah dalam Perspektif Majelis Tarjih Alquran (MTA) - Sukron, Mokhamad (Religió: Jurnal Studi Agama-agama, 2015)
Falsehood (bid‘ah) becomes an interesting study for Moslem scholars especially on the matters of worship and ritual practices. The committee of tarjîh al-Qur’ân justifies falsehood by referring to H{adith used as the guide and method. The interpretative result toward the h}adith causes different perspective among Moslem scholars. There are three important points that will be elucidated in this article: first what method uses MTA in conceiving h}adith in relation with falsehood, second how MTA perspective of bid‘ah, and third is re-construction the h}adith bid‘ah according to MTA. MTA explains that what is called bid‘ah in prophet’s h}adith is bid‘ah in the matter of religion (worship) that certainly misleading. Yet, the falsehood in relation with worldly matter for MTA must be given a space to branch out as long as it gives positive impact and push people creativity in general meaning. It is suitable with prophet’s h}adith said that “man sanna sunnah h}asanah..... man sanna sunnah sayyiah...”. In this condition, MTA indirectly admits the variant of the bid‘ah. But the ordinary classification differs with the ulama’s classification either in terms of mutaqadimîn or muta’akhirîn, in general point of view, otherwise the classification is in contrary with the religious matters and worldly matters.